Flexuous, threadlike particles in leaf cells of Echinocloa colonum infected with rice hoja blanca virus - Kitajima, Elliot W.; Gálvez E., Guillermo E. (1973)
Electron microscopic examination of thin section from rice hoja blanca virus (RHBV)-infected barnyard [Echinocloa colonum (L.) Link] revealed the occurrence of large masses of flexuous, tubular particles, 8-10 nm wide, both in the cytoplasm and nucleus. These inclusions were absent in cells from healthy plants. This observation is consistent with previous studies with RHBV-infected rice cells and viruliferous leafhopper vector (Sogatodes oryzicolus) tissues, and reinforces the view that these elongated particles represent the RHBV in situ